PRIVIRE GENERALĂ ASUPRA FENOMENULUI VIOLENŢEI ÎN FAMILIE - USM ADMIN (Studia Universitatis Moldaviae: Stiinte ale Educatiei, 2007)
Violence has bad consequences (social, economic, psychological, etc.) as for women and children as well for men. The tolerance of violence acceptable in many countries once again shows the necessity of changing of gender role in society and gender stereotypes. Such changes well do towards the prevention of violent, abusive behavior in gender relationship.